An Analysis of Self Directed Learning of the English Major Students and the Non-English Major Students of IAIN Parepare in Learning English - Nur Yastad Fajrah; Arqam; Magdahalena Tjalla; Abd Haris Sunubi; Ambo Dalle (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
Self-Directed Learning is Process in which learners take the initiative to manage their own plan in learning by using any resources, strategy or method to show their personal goals. This study aims to figure out how is the self-directed learning of the English major student and the Non-English major of IAIN Parepare in learning English and the dominant factor in influencing student’s self-directed learning. This research applied a qualitative descriptive as the research design. In collecting the data, the researcher applied interviews and documentation. The data analysis technique uses Miles and Huberman. Data Analysis, which has four steps the steps was data collection, data reduction, data display and conclusion and verification. The results showed that students of English major and Non-English major similar in conducted self-directed learning by utilizing internet, listening music, translation applications, and watching movies. The researcher found that the students practiced it in their daily life which made them able to learn. Self- Directed Learning is very good to be applied in every situation because students can learn by themselves without the help of teachers or other people to learn English. only by using social media on their mobile phones and laptops to learn independently. Then, there were 2 dominant factors influenced self-directed learning of English major student and Non-English major students in learning English, they were: a) how to learn (internal factor), b) study time (external factor).